Changes in flood mortality during the last 50 years in Greece. - Diakakis, M.; Deligiannakis, G. (Bulletin of the Geological Society of Greece, 2013)
This work focuses on the changes that occur in the circumstances under which flood fatalities occur in Greece. To this aim, this paper develops and studies a database of 189 flood-related deaths, between 1960 and 2010, consisting of variables describing the conditions during the time of each incident. Changes in the number and the spatial distribution of fatalities, together with changes in the conditions, the surrounding environment and the demographics of the victims are investigated. Results showed that males, youngsters and elderly people presented an overrepresentation among the decedents, although individuals between 20 and 65 showed a significant increase among the victims, especially during the last decades of the study period. Fatal flood events were found to be approximately equally divided between urban and rural environments. However, fatal incidents appear to gradually migrate from urban centers to rural environments. Vehicle-related fatalities showed a gradual increase, whereas pedestrian victims and indoors incidents show an opposite trend. Fatalities per flood event presented a significant decline, although in absolute numbers, flood deaths did not show a respectively important decreasing trend. Among different causes of death drowning was found to be the most common throughout the study period.